Efficient transformation of the medicinal mushroomGanoderma lucidum - Li Sun; Huaqing Cai; Weihong Xu; Yuanlei Hu; Yin Gao; Zhongping Lin (Plant Molecular Biology Reporter, 2001)

A rapid and efficient DNA minipreparation suitable for screening transgenic plants - Rong-Cheng Lin; Zai-Song Ding; Liang-Bi Li; Ting-Yun Kuang (Plant Molecular Biology Reporter, 2001)

Early genes responsive to abscisic acid during heterophyllous induction in Marsilea quadrifolia - Ting-Chang Hsu; Hung-Chi Liu; Jang-Shiun Wang; Rung-Wu Chen; Ying-Chuan Wang; Bai-Ling Lin (Plant Molecular Biology, 2001)

The role of thiol compounds in increasing Agrobacterium-mediated transformation of soybean cotyledonary-node cells - P. Olhoft; K. Lin; J. Galbraith; N. Nielsen; D. Somers (Plant Cell Reports, 2001)

Transdermal Delivery of Antisense Oligonucleotides with Microprojection Patch (macroflux®) Technology - WeiQi Lin; Michel Cormier; Ahmad Samiee; Angie Griffin; Bonny Johnson; Ching-Leou Teng; Gregory E. Hardee; Peter E. Daddona (Pharmaceutical Research, 2001)

Protection against translocating Salmonella typhimurium infection in mice by feeding the immuno-enhancing probiotic Lactobacillus rhamnosus strain HN001 - Harsharnjit S. Gill; Quan Shu; Hai Lin; Kay J. Rutherfurd; Martin L. Cross (Medical Microbiology and Immunology, 2001)

Reproduction in a simultaneous hermaphroditic shrimp, Lysmata wurdemanni : any two will do? - Lin J.; Zhang D. (Marine Biology, 2001)

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes - Yu-Chia Chen; Shieh-Shiuh Kung; Bo-Yuan Chen; Chi-Chang Hung; Chun-Chen Chen; Tzi-Yuan Wang; Yi-Mi Wu; Wei-Hsiang Lin; Chyng-Shyan Tzeng; Wei-Yuan Chow (Journal of Molecular Evolution, 2001)

PCR Genome Walking Identifies a Genetic Locus Comprising Two Heat Shock Genes (hslV and hslU) from Leptospira borgpetersenii Serovar Hardjobovis - Min Lin; Yijing Li (Current Microbiology, 2001)

Thallium Concentration in Lake Trout from Lake Michigan - T.-S. Lin; J. Nriagu; X.-Q. Wang (Bulletin of Environmental Contamination and Toxicology, 2001)

Regio- and stereo-selective synthesis of vinyl glucose ester catalyzed by an alkaline protease of Bacillus subtilis - Qi Wu; Deshui Lu; Ying Cai; Xingtao Xue; Zhichun Chen; Xianfu Lin (Biotechnology Letters, 2001)

Temporal selectivity by single neurons in the torus semicircularis of Batrachyla antartandica (Amphibia: Leptodactylidae) - Mario Penna; Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Cloning, Tissue Expression Pattern, and Chromosome Location of a Novel Human Gene BRI3BP - Lizhu Lin; Yimin Wu; Changben Li; Shouyuan Zhao (Biochemical Genetics, 2001)

A case modeling of sea–land breeze in macao and its neighborhood - Lin Wenshi; Wang Anyu; Wu Chisheng; Fong Soi Kun; Ku Chimeng (Advances in Atmospheric Sciences, 2001)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Identification of a Region Critically Involved in the Interaction of Phlorizin with the Rabbit Sodium-D-Glucose Cotransporter SGLT1 - R. Novakova; D. Homerova; R.K.H. Kinne; E. Kinne-Saffran; J.T. Lin (The Journal of Membrane Biology, 2001)

Relative importance of Na+, Cl−, and abscisic acid in NaCl induced inhibition of root growth of rice seedlings - Chuan Chi Lin; Ching Huei Kao (Plant and Soil, 2001)

Trophic functioning and nutrient flux in a highly productive tropical lagoon - Hsing-Juh Lin; Jia-Jang Hung; Kwang-Tsao Shao; Fancy Kuo (Oecologia, 2001)

Plasmids carrying cloned fragments of RF DNA from the filamentous phage φLf can be integrated into the host chromosome via site-specific integration and homologous recombination - N.-T. Lin; R.-Y. Chang; S.-J. Lee; Y.-H. Tseng (Molecular Genetics and Genomics, 2001)

Reproduction in a simultaneous hermaphroditic shrimp, Lysmata wurdemanni : any two will do? - Lin J.; Zhang D. (Marine Biology, 2001)

Unexpectedly high coral coverage in Chinwan Inner Bay, Pescadores: a proposed site for a Marine Protection Area - Hernyi Hsieh; Nuwei Wei; Yi-lin Lu; Ming-Shiu Jeng; Wan-Shen Tsai; Chaolun Chen (Coral Reefs, 2001)

Prospective study of tooth loss and incident esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Free-field unmasking response characteristics of frog auditory nerve fibers: comparison with the responses of midbrain auditory neurons - Wen-Yu Lin; Albert Feng (Journal of Comparative Physiology A, 2001)

Cultures of equine respiratory epithelial cells and organ explants as tools for the study of equine influenza virus infection - C. Lin; R. E. Holland Jr; N. M. Williams; T. M. Chambers (Archives of Virology, 2001)

Rapid molecular analysis of the haemagglutinin gene of human influenza A H3N2 viruses isolated in Spain from 1996 to 2000 - M. T. Coiras; J. C. Aguilar; M. Galiano; S. Carlos; V. Gregory; Y. P. Lin; A. Hay; P. Pérez-Breña (Archives of Virology, 2001)

Dependence of Papanicolaou gradings of exfoliated urothelial cells upon GSTM1 and GSTT1 polymorphism in benzidine-exposed workers of the Shanghai dye industry - Guofang Lin; Qingwen Ma; Jigang Chen; Jianhua Shen; Cuiqing Xiang; Klaus Golka; Dongsheng Zhang (Archives of Toxicology, 2001)

Time-Frequency Analysis of Heart Rate Variability During Transient Segments - Hsiao-Lung Chan; Hui-Hsun Huang; Jiunn-Lee Lin (Annals of Biomedical Engineering, 2001)

Nutritive quality and morphological development under partial shade of some forage species with agroforestry potential - C. H. Lin; M. L. McGraw; M. F. George; H. E. Garrett (Agroforestry Systems, 2001)

Development of the Fragment Constant Method for Estimating the Partition Coefficients of Nonionic Organic Mixtures - Z. Lin, H. Yu, S. Gao, J. Cheng, L. Wa (Archives of Environmental Contamination and Toxicology, 2001)

X-ray absorption spectroscopy study shows that the rapid selenium volatilizer, pickleweed (Salicornia bigelovii Torr.), reduces selenate to organic forms without the aid of microbes - A. Lee; Z.-Q. Lin; I. Pickering; N. Terry (Planta, 2001)

Stopped-flow kinetic study of the H2O2 oxidation of substrates catalyzed by microperoxidase-8 - Hui-Chun Yeh; Jinn-Shyan Wang; Oliver Y. Su; Wann-Yin Lin (JBIC Journal of Biological Inorganic Chemistry, 2001)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Genetic analysis of cold tolerance during vegetative growth in tomato, Lycopersicon esculentum Mill. - M.R. Foolad; G.Y. Lin (Euphytica, 2001)

Exploring suitability for tropical crop cultivation in Hainan Island by SOTAL methodology - Zhang Xue-lei; S. Mantel; Zhang Gan-lin; V. W. P. van Engelen (Journal of Geographical Sciences, 2001)

Software GPS Receiver - Vasu Chakravarthy; James Tsui; David Lin; John Schamus (GPS Solutions, 2001)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

Environmental Exposure to Polycyclic Aromatic Hydrocarbons and Total Suspended Particulates in a Taiwanese Temple - T-C. Lin; F-H. Chang; J-H. Hsieh; H-R. Chao; M-R. Chao (Bulletin of Environmental Contamination and Toxicology, 2001)

Neurotoxicity of mercury sulfide in the vestibular ocular reflex system of guinea pigs - Jiunn-Jye Chuu; Yi-Ho Young; Shing-Hwa Liu; Shoei-Yn Lin-Shiau (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)

Production of fructooligosaccharides in high yield using a mixed enzyme system of β-fructofuranosidase and glucose oxidase - Dey Chyi Sheu; Po Jang Lio; Shih Tse Chen; Chi Tsai Lin; Kow Jen Duan (Biotechnology Letters, 2001)

Separation of different sized particles by inertial migration - S.R. Wickramasinghe; W.-C. Lin; D.S. Dandy (Biotechnology Letters, 2001)

Identification of estrogen-responsive genes in chick liver - Yunfeng Zhu; Mei Wang; Hong Lin; Zheng Li; Jia Luo (Cell and Tissue Research, 2001)

Ultrasonic Wave Propagation in Trabecular Bone Predicted by the Stratified Model - Wei Lin; Yi-Xian Qin; Clinton Rubin (Annals of Biomedical Engineering, 2001)

On the Formation and Maintenance of the Persistent Anomalies of Summertime Circulation over the Ural Mountains - Li Shuanglin; Ji Liren; Lin Wantao (Advances in Atmospheric Sciences, 2001)

Recent Researches on the Short-Term Climate Prediction at IAP—A Brief Review - Wang Huijun; Zhou Guangqing; Lin Zhaohui; Zhao Yan; Guo Yufu; Ma Zhuguo (Advances in Atmospheric Sciences, 2001)

In vitro and in vivo evaluations of biodegradable implants for hormone replacement therapy: Effect of system design and PK-PD relationship - Senshang Lin; Pi-Yun Chao; Yie W. Chien; Amyn Sayani; Sandeep Kumar; Michelle Mason; Thomas West; Alice Yang; Donald Monkhouse (AAPS PharmSciTech, 2001)

Pharmaceutical development and manufacturing of a parenteral formulation of a novel antitumor agent, VNP40101M - Gopal Krishna; William F. Hodnick; Wengsheng Lang; Xu Lin; Srinivasa Karra; John Mao; Bijan Almassian (AAPS PharmSciTech, 2001)

Deformation mechanisms and fluid behavior in a shallow, brittle fault zone during coseismic and interseismic periods: Results from drill core penetrating the Nojima Fault, Japan - Hidemi Tanaka; Shin‐Ichiro Hinoki; Kazuo Kosaka; Aiming Lin; Keiji Takemura; Akihiro Murata; Takao Miyata (Island Arc, 2001)
This paper describes the results of petrographical and meso‐ to microstructural observations of brittle fault rocks in cores obtained by drilling through the Nojima Fault at a drilling depth of 389.52 m. The zonation of deformation and alteration in the central zone of the fault is clearly seen in cores of granite from the hanging wall, in the following order: (i) host rock, which is characterized by some intragranular microcracks and in situ alteration of mafic minerals and feldspars; (ii) weakly deformed and altered rocks, which are characterized by transgranular cracks and the dissolution of mafic minerals, and by the precipitation of zeolites and iron hydroxide materials; (iii) random fabric fault breccia, which is characterized by fragmentation, by anastomosing networks of transgranular cracks, and by the precipitation of zeolites and iron hydroxide materials; and (iv) fault gouge, which is characterized by the precipitation of smectite and localized cataclastic flow. This zonation implies that the fault has been weakened gradually by fluid‐related fracturing over time. In the footwall, a gouge layer measuring only 15 mm thick is present just below the surface of the Nojima Fault. These observations are the basis for a model of fluid behavior along the Nojima Fault. The model invokes the percolation of meteoric fluids through cracks in the hanging wall fault zone during interseismic periods, resulting in chemical reactions in the fault gouge layer to form smectite. The low permeability clay‐rich gouge layer sealed the footwall. The fault gouge was brecciated during coseismic or postseismic periods, breaking the seal and allowing fluids to readily flow into the footwall, thus causing a slight alteration. Chemical reactions between fluids and the fault breccia and gouge generated new fault gouge, which resealed the footwall, resulting in a low fluid condition in the footwall during interseismic periods.

Quaternary vertical offset and average slip rate of the Nojima Fault on Awaji Island, Japan - Akihiro Murata; Keiji Takemura; Takao Miyata; Aiming Lin (Island Arc, 2001)

Comparative study of cataclastic rocks from a drill core and outcrops of the Nojima Fault zone on Awaji Island, Japan - Aiming Lin; Toshihiko Shimamoto; Tadashi Maruyama; Motoko Sigetomi; Takao Miyata; Keiji Takemura; Hidemi Tanaka; Shinichi Uda; Akihiro Murata (Island Arc, 2001)
Cataclastic rocks found in the Disaster Prevention Research Institute, Kyoto University (DPRI) 500 m drill core and outcrops along the Nojima Fault zone on Awaji Island, southwest Japan, were examined at mesoscopic and microscopic scales. The damaged zone of this fault in granitic rocks, observed on the southeast side of the fault, is 50–60 m wide and is composed of fractured host rocks and cataclastic rocks including cataclasite, fault breccia, and fault gouge. The fault breccia and gouge of small scales are scattered in the damaged zone. Fault core (zone of extremely concentrated shearing deformation along a fault) consists of fault gouge measuring several tens to approximately 150 mm in width, as recognized both in the drill core and at outcrops of the Nojima Fault along which surface ruptures formed during the 1995 Kobe earthquake. Fault breccia, measuring a few meters wide, has developed pervasively in the damaged zone, just next to the fault core. Pseudotachylyte has been found interlayered with fault gouge within the fault core only at outcrops at Hirabarashi, not in the DPRI 500 m core. Petrological studies and powder X‐ray diffraction analysis show that the pseudotachylyte and fault gouge are composed mainly of fine‐grained angular clasts of the host granitic rocks, suggesting the pseudotachylyte is of ‘crush origin’. Foliated cataclasite is characterized by the preferred orientation of elongated biotite clasts and granular aggregates of quartz and feldspar clasts, and by the development of cataclastic shear bands. Unlike cataclastically deformed quartz and feldspar in the cataclasite, biotite in the foliated cataclasite shows combinations of brittle and plastic deformation, such as biotite ‘fish’, cleavage steps, bending and kinking. These textures suggest that the foliated cataclasite formed at a deeper level than the cataclasite, fault breccia and gouge, possibly before the Quaternary period during which the Nojima Fault has moved as a dextral strike–slip fault with some reverse movement resulting in the uplifting of Awaji Island. Examination of fault rocks from surface outcrops can yield similar results to those obtained from drill cores with regard to the internal structures of a fault zone.

Crack-filling clays and weathered cracks in the DPRI 1800 m core near the Nojima Fault, Japan: Evidence for deep surface-water circulation near an active fault - Shin-Ichi Uda; Aiming Lin; Keiji Takemura (Island Arc, 2001)

Deformation mechanisms and fluid behavior in a shallow, brittle fault zone during coseismic and interseismic periods: Results from drill core penetrating the Nojima Fault, Japan - Hidemi Tanaka; Shin-Ichiro Hinoki; Kazuo Kosaka; Aiming Lin; Keiji Takemura; Akihiro Murata; Takao Miyata (Island Arc, 2001)

Crack‐filling clays and weathered cracks in the DPRI 1800 m core near the Nojima Fault, Japan: Evidence for deep surface‐water circulation near an active fault - Shin‐Ichi Uda; Aiming Lin; Keiji Takemura (Island Arc, 2001)
Crack‐filling clays and weathered cracks were observed in the Disaster Prevention Research Institute, Kyoto University (DPRI) 1800 m cores drilled from the Nojima Fault Zone, which was activated during the 1995 Hyogo‐ken Nanbu earthquake (Kobe earthquake). The crack‐filling clays consist mainly of unconsolidated fine‐grained materials that fill opening cracks with no shear textures. Most of the cracks observed in the DPRI 1800 m cores are yellow‐brown to brown in color due to weathering. Powder X‐ray diffraction analyses show that the crack‐filling clays are composed mainly of clay minerals and carbonates such as siderite and calcite. Given that the top of the borehole is approximately 45 m above sea level, most of the core is far below the stable groundwater table. Hence, it is suggested that the crack‐filling clays and weathered cracks in the cores taken at depths of 1800 m were formed by the flow of surface water down to the deep fractured zone of the Nojima Fault Zone during seismic faulting.

Quaternary vertical offset and average slip rate of the Nojima Fault on Awaji Island, Japan - Akihiro Murata; Keiji Takemura; Takao Miyata; Aiming Lin (Island Arc, 2001)
Drilling was carried out to penetrate the Nojima Fault where the surface rupture occurred associated with the 1995 Hyogo‐ken Nanbu earthquake. Two 500 m boreholes were successfully drilled through the fault zone at a depth of 389.4 m. The drilling data show that the relative uplift of the south‐east side of the Nojima Fault (south‐west segment) was approximately 230 m. The Nojima branch fault, which branches from the Nojima Fault, is inferred to extend to the Asano Fault. From the structural contour map of basal unconformity of the Kobe Group, the vertical component of displacement of the Nojima branch–Asano Fault is estimated to be 260–310 m. Because the vertical component of displacement on the Nojima Fault of the north‐east segment is a total of those of the Nojima Fault of the south‐west segment and of the Nojima branch–Asano Fault, it is estimated to total to 490–540 m. From this, the average vertical component of the slip rate on the Nojima Fault is estimated to be 0.4–0.45 m/10 3 years for the past 1.2 million years.

Comparative study of cataclastic rocks from a drill core and outcrops of the Nojima Fault zone on Awaji Island, Japan - Aiming Lin; Toshihiko Shimamoto; Tadashi Maruyama; Motoko Sigetomi; Takao Miyata; Keiji Takemura; Hidemi Tanaka; Shinichi Uda; Akihiro Murata (Island Arc, 2001)

( R )-Methanandamide and Δ 9 -THC as discriminative stimuli in rats: tests with the cannabinoid antagonist SR-141716 and the endogenous ligand anandamide - Järbe T.; Lamb R.; Lin S.; Makriyannis A. (Psychopharmacology, 2001)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Geology and structural controls of the Twin Peaks epithermal gold deposit, East Junggar, Xinjiang, China - Chunzeng Wang; Jinfu Lin; Kaiqiu Dai (Mineralium Deposita, 2001)

Molecular differentiation of two morphological variants of Gracilaria salicornia - Phaik-Eem Lim; Kwai-Lin Thong; Siew-Moi Phang (Journal of Applied Phycology, 2001)

A juvenile ankylosaur from China - Xing Xu; Xiao-Lin Wang; Hai-Lu You (The Science of Nature, 2001)

Plant species effect on the spatial patterns of soil properties in the Mu-us desert ecosystem, Inner Mongolia, China - Muneto Hirobe; Nobuhito Ohte; Nanae Karasawa; Guo-sheng Zhang; Lin-he Wang; Ken Yoshikawa (Plant and Soil, 2001)

RS-100642-198, a novel sodium channel blocker, provides differential neuroprotection against hypoxia/hypoglycemia, veratridine or glutamate-mediated neurotoxicity in primary cultures of rat cerebellar neurons - Jitendra R. Dave; Yu Lin; Haresh S. Ved; Michael L. Koenig; Larry Clapp; John Hunter; Frank C. Tortella (Neurotoxicity Research, 2001)

Comparative physical mapping of targeted regions of the rat genome - Tyrone J. Summers; James W. Thomas; Shih-Queen Lee-Lin; Valerie V.B. Maduro; Jacquelyn R. Idol; Eric D. Green (Mammalian Genome, 2001)

Multiple-Point Variance Analysis for Optimal Adjustment of a Monitoring Network - Yu-Pin Lin; Shaharokh Rouhani (Environmental Monitoring and Assessment, 2001)

The effect of specific growth rates on the recovery of amino acids - Yupeng Zhao; Yen-Han Lin (Biotechnology Letters, 2001)

Enantioselective production of levofloxacin by immobilized porcine liver esterase - Sang-Yoon Lee; Byung-Hyuk Min; Sung-Ho Hwang; Yoon-Mo Koo; Choul-Kyun Lee; Seong-Won Song; Sun-Young Oh; Sang-Min Lim; Sang-Lin Kim; Dong-II Kim (Biotechnology Letters, 2001)

Characterization of stress-responsive genes, hrcA-grpE-dnaK-dnaJ , from phytopathogenic Xanthomonas campestris - Shu-Fen Weng; Pan-Ming Tai; Cheng-Hwa Yang; Cheng-Der Wu; Wan-Ju Tsai; Juey-Wen Lin; Yi-Hsiung Tseng (Archives of Microbiology, 2001)

Construction of explicit quasi-Complete square conservative difference schemes of forced dissipative nonlinear evolution equations - Lin Wantao; Ji Zhongzhen; Wang Bin (Advances in Atmospheric Sciences, 2001)

Bioaccumulation of Arsenic in Aquacultural Large-Scale Mullet Liza macrolepis from Blackfoot Disease Area in Taiwan - M.-C. Lin; C.-M. Liao; C.-W. Liu; S. Singh (Bulletin of Environmental Contamination and Toxicology, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

The N-Terminal Signal Sequence and the Last 98 Amino Acids Are Not Essential for the Secretion of Bacillus sp. TS-23 α-Amylase in Escherichia coli - Huei-Fen Lo; Long-Liu Lin; Chien-Cheng Li; Wen-Hwei Hsu; Chen-Tien Chang (Current Microbiology, 2001)

Hazardous Air Pollutant Source Emissions for a Chemical Fiber Manufacturing Facility in Taiwan - Chi-Wen Lin (Water, Air, & Soil Pollution, 2001)

Distribution of glucose-6-phosphate dehydrogenase mutations in Southeast Asia - Kuni Iwai; Akira Hirono; Hiroyuki Matsuoka; Fumihiko Kawamoto; Toru Horie; Khin Lin; Indah S. Tantular; Yoes P. Dachlan; Harsono Notopuro; Noor I. Hidayah; Abdul M. Salim; Hisaichi Fujii; et al. (Human Genetics, 2001)

A natural-gradient field tracer test for evaluation of pollutant-transport parameters in a porous-medium aquifer - Y. Yang; X. Lin; T. Elliot; R. Kalin (Hydrogeology Journal, 2001)

Identification of Essential Cysteine Residues in 3-Deoxy-d-Arabino-Heptulosonate-7-Phosphate Synthase from Corynebacterium glutamicum - Long-Liu Lin; Hui-Fen Liao; Hungchien Roger Chien; Wen-Hwei Hsu (Current Microbiology, 2001)

The remarkable hydrophobic effect of a fatty acid side chain on the microbial growth promoting activity of a synthetic siderophore - Yun-Ming Lin; Marvin J. Miller; Ute Möllmann (BioMetals, 2001)

Study on methods of land use dynamic monitoring at county level - Lin-yi Li; Fang Huang; Zhao-li Liu; En-pu Wan (Chinese Geographical Science, 2001)

Genetic Diversity among Different Clones of the Gynogenetic Silver Crucian Carp, Carassius auratus gibelio, Revealed by Transferrin and Isozyme Markers - Lin Yang; Shu-Ting Yang; Xue-Hong Wei; Jian-Fang Gui (Biochemical Genetics, 2001)

Long-term monitoring of the coral reef fish communities around a nuclear power plant - Rong-Quen Jan; Jeng-Ping Chen; Chun-Yu Lin; Kwang-Tsao Shao (Aquatic Ecology, 2001)

High-pressure Raman spectroscopic study of Co- and Ni-olivines - C. C. Lin (Physics and Chemistry of Minerals, 2001)

Tamoxifen-induced Ca 2+ mobilization in bladder female transitional carcinoma cells - Hong-Tai Chang; Jong-Khing Huang; Jue-Long Wang; Jin-Shiung Cheng; Kam-Chung Lee; Yuk-Keung Lo; Muh-Chiou Lin; Kwong-Yui Tang; Chung-Ren Jan (Archives of Toxicology, 2001)

The C-terminal part of the R-domain, but not the PDZ binding motif, of CFTR is involved in interaction with Ca 2+ -activated Cl - channels - Lin Wei; Anne Vankeerberghen; Harry Cuppens; Jean-Jacques Cassiman; Guy Droogmans; Bernd Nilius (Pflügers Archiv - European Journal of Physiology, 2001)

Toward the mapping of physiological and agronomic characters on a rice function map: QTL analysis and comparison between QTLs and expressed sequence tags - K. Ishimaru; M. Yano; N. Aoki; K. Ono; T. Hirose; S. Y. Lin; L. Monna; T. Sasaki; R. Ohsugi (Theoretical and Applied Genetics, 2001)

Pharmacokinetics of reboxetine in healthy volunteers with different ethnic descents - Pamela E. Hendershot; Joseph C. Fleishaker; Keh-Ming Lin; Inocencia D. Nuccio; Russell E. Poland (Psychopharmacology, 2001)

Stable cell lines expressing baculovirus P35: Resistance to apoptosis and nutrient stress, and increased glycoprotein secretion - Guangyun Lin; Guoxun Li; Robert R. Granados; Gary W. Blissard (In Vitro Cellular & Developmental Biology - Animal, 2001)

Development and characterization of common wheat-Thinopyrum intermedium translocation lines with resistance to barley yellow dwarf virus - Z.Y. Xin; Z.Y. Zhang; X. Chen; Z.S. Lin; Y.Z. Ma; H.J. Xu; P.M. Banks; P.J. Larkin (Euphytica, 2001)

Toxicokinetics and Acute Toxicity of Waterborne Zinc in Abalone ( Haliotis diversicolor supertexta Lischke) - C.-M. Liao; M.-C. Lin (Bulletin of Environmental Contamination and Toxicology, 2001)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)

Production and purification of recombinant Blomia tropicalis group 5 allergen from Pichia pastoris culture - Lin-Tang Goh; I-Chun Kuo; Sa Luo; Kaw Yan Chua; Moshe White (Biotechnology Letters, 2001)

Genetic transformation of duckweed Lemna gibba and Lemna minor - Yuri T. Yamamoto; Nirmala Rajbhandari; Xiaohong Lin; Ben A. Bergmann; Yufuko Nishimura; Anne-Marie Stomp (In Vitro Cellular & Developmental Biology - Plant, 2001)

Indigenous community forest management of Jinuo people's swidden agroecosystems in southwest China - Chun-Lin Long; Yilan Zhou (Biodiversity and Conservation, 2001)

Modelling the global monsoon system by IAP 9L AGCM - Xue Feng; Bi Xunqiang; Lin Yihua (Advances in Atmospheric Sciences, 2001)

Problems of nonlinear computational instability in evolution equations - Ji Zhongzhen; Lin Wantao; Yang Xiaozhong (Advances in Atmospheric Sciences, 2001)

Computational stability of the explicit difference schemes of the forced dissipative nonlinear evolution equations - Lin Wantao; Ji Zhongzhen; Wang Bin (Advances in Atmospheric Sciences, 2001)

Heterotrimeric G-protein and signal transduction in the nematode-trapping fungus Arthrobotrys dactyloides - Tsung-Hsien Chen; Chan-San Hsu; Pui-Jen Tsai; Yi-Feng Ho; Na-Sheng Lin (Planta, 2001)

Eco-environmental problems and effective utilization of water resources in the Kashi Plain, western Terim Basin, China - Nian-Feng Lin; Jie Tang; Feng-Xiang Han (Hydrogeology Journal, 2001)

Stimulation effect of gibberellic acid short-term treatment on leaf photosynthesis related to the increase in Rubisco content in broad bean and soybean - Lin Yuan; Da-Quan Xu (Photosynthesis Research, 2001)

Characterization of a SINE species from vicuna and its distribution in animal species including the family Camelidae - Z. Lin; O. Nomura; T. Hayashi; Y. Wada; Hiroshi Yasue (Mammalian Genome, 2001)

Cyanide-Induced Alterations to the Biophysical Conformations of the Isolated Fish Liver - Yih-Dih Cheng; Tsung-Yun Liu; Shan-Yang Lin (Ecotoxicology, 2001)

Decolorization kinetics of a recombinant Escherichia coli strain harboring azo-dye-decolorizing determinants from Rhodococcus sp. - Jo-Shu Chang; Chia-Yu Lin (Biotechnology Letters, 2001)

Electrochemical Treatment of Pyrrhotite-rich Tailings–a Laboratory Study - Mei Lin; Leonard Seed; Ward Chesworth; Joseph Fyfe; Rejean Brousseau; Gene Shelp (Mine Water and the Environment, 2001)

Sandy desertification trend in western Northeast China Plain in the past 10 years - Li Bao-lin; Zhou Cheng-hu (Journal of Geographical Sciences, 2001)

Design of environmental decision support system and its application to water quality management - Zeng Fan-tang; Du Ling; Lin Kui; Shen Qian (Journal of Geographical Sciences, 2001)

Water resources optimization and eco-environmental protection in Qaidam Basin - Fang Chuang-lin; Bao Chao (Journal of Geographical Sciences, 2001)

G561 site-directed deletion mutant chitinase from Aeromonas caviae is active without its 304 C-terminal amino acid residues - Fu-Pang Lin; Woan-Yuan Juang; Keng-Hao Chang; Hsing-Chen Chen (Archives of Microbiology, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

UV-Induced Increase in RNA Polymerase Activity in Xanthomonas oryzae pathovar oryzae - Shan-Hua Lin; Hao-Jen Huang; Bei-Chang Yang; Tsong-Teh Kuo (Current Microbiology, 2001)

Cell wall peroxidase activity, hydrogen peroxide level and NaCl-inhibited root growth of rice seedlings - Chuan Chi Lin; Ching Huei Kao (Plant and Soil, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – I. Slightly unstable and neutral cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Large-Eddy Simulations of the Atmospheric Boundary Layer Using a New Subgrid-Scale Model – II. Weakly and moderately stable cases - Feng Ding; S. Pal Arya; Yuh-Lang Lin (Environmental Fluid Mechanics, 2001)

Effects of Laundering upon the Removal of Atrazine and Metolachlor from Cotton, Cotton/Polyester, and Polyester Fabrics Treated with Fluorochemical Finishes - A. Shaw; Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Translational Regulation as a Novel Mechanism for the Development of Cellular Drug Resistance - John C. Schmitz; Jun Liu; Xiukun Lin; Tian-min Chen; Wu Yan; Ningwen Tai; Ashwin Gollerkeri; Edward Chu (Cancer and Metastasis Reviews, 2001)

Social polarization and segregation in Beijing - Chao-lin Gu (Chinese Geographical Science, 2001)

Statistical optimization of gastric floating system for oral controlled delivery of calcium - Shoufeng Li; Senshang Lin; Yie W. Chien; Bruce P. Daggy; Haresh L. Mirchandani (AAPS PharmSciTech, 2001)

Allozyme variations in Michelia formosana (Kanehira) Masamune(Magnoliaceae), and the inference of a glacial refugium in Taiwan - T.-P. Lin (Theoretical and Applied Genetics, 2001)

Time-dependent responses of soil CO2 efflux components to elevated atmospheric [CO2] and temperature in experimental forest mesocosms - Guanghui Lin; Paul T. Rygiewicz; James R. Ehleringer; Mark G. Johnson; David T. Tingey (Plant and Soil, 2001)

Litter decomposition and nitrogen mineralization of soils in subtropical plantation forests of southern China, with special attention to comparisons between legumes and non-legumes - Zhi-an Li; Shao-lin Peng; Debbie J. Rae; Guo-yi Zhou (Plant and Soil, 2001)

Chemical characters and antioxidative properties of sulfated polysaccharides from Laminaria japonica - Chang-Hu Xue; Yu Fang; Hong Lin; Lei Chen; Zhao-Jie Li; Deng Deng; Chong-Xiao Lu (Journal of Applied Phycology, 2001)

Validation of IAP94 land surface model over the Huaihe River basin with HUBEX field experiment data - Yang Xiaosong; Lin Zhaohui; Dai Yongjiu; Guo Yufu (Advances in Atmospheric Sciences, 2001)

The maintenance of the blocking over the ural mountains during the second Meiyu period in the summer of 1998 - Li Shuanglin; Ji Liren; Lin Wantao; Ni Yunqi (Advances in Atmospheric Sciences, 2001)

Functional Asymmetry of the Sodium- d -Glucose Cotransporter Expressed in Yeast Secretory Vesicles - M.A. Firnges; J.-T. Lin; R.K.-H. Kinne (The Journal of Membrane Biology, 2001)

Postnatal development of biotinylated dextran amine-labeled corpus callosum axons projecting from the visual and auditory cortices to the visual cortex of the rat - Song-Lin Ding; Andrea J. Elberger (Experimental Brain Research, 2001)

Birth seasonality and interbirth intervals in free-ranging formosan macaques,Macaca cyclopis, at Mt. Longevity, Taiwan - Minna J. Hsu; Govindasamy Agoramoorthy; Jin-Fu Lin (Primates, 2001)

STABLE CELL LINES EXPRESSING BACULOVIRUS P35: RESISTANCE TO APOPTOSIS AND NUTRIENT STRESS, AND INCREASED GLYCOPROTEIN SECRETION - GUANGYUN LIN; GUOXUN LI; ROBERT R. GRANADOS; GARY W. BLISSARD (In Vitro Cellular & Developmental Biology - Animal, 2001)

Characterization of grouper nervous necrosis virus (GNNV) - S C Chi; B J Lo; S C Lin (Journal of Fish Diseases, 2001)
Grouper nervous necrosis virus (GNNV) was isolated from moribund grouper larvae, Epinephelus sp., using a fish cell line GF‐1. The present study describes the biochemical and biophysical properties of GNNV and the expression of GNNV in diseased grouper larvae. Viral protein was detectable in most of the GNNV‐infected GF‐1 cells by the fluorescent antibody technique (FAT) after 12 h post‐infection (p.i.), although no cytopathic effect (CPE) appeared at that time. Clear CPE developed on the third day, and complete disintegration of the monolayer occurred over the subsequent two days. The infectivity of GNNV can be blocked following treatment at 60 °C for 1 h. GNNV was sensitive to pH 3 and pH 10–12 with a 4 log 10 drop in infectivity. Purified GNNV was analysed by SDS–PAGE, and then stained with periodic acid silver. The positive staining indicated that its two capsid proteins were glycoproteins. Genomic RNAs of GNNV were extracted from purified virions and analysed. The molecular weights of genomic RNAs were 1.02 × 10 6 and 0.50 × 10 6 Da. The T2 region of the coat protein gene of GNNV was amplified by polymerase chain reaction (PCR), and the multiple alignment of the T2 sequence of two GNNV isolates with four genotypes of fish nodaviruses revealed that these two isolates (GNNV9410 and GNNV9508) belong to the red‐spotted grouper nervous necrosis virus (RGNNV) genotype. The tissue distribution of GNNV in naturally infected grouper larvae was investigated by in situ hybridization using a dig‐labelled probe, which showed that GNNV was not only detected in the brain and retina, but also in the gill, skeletal muscle, liver, pyloric gland, intestine and blood cells in the heart.